Isolation and characterization of elapitoxin-Bf1b, a postsynaptic neurotoxin from Malaysian Bungarus fasciatus venom - Rusmili, M.R.A.; Yee, T.T.; Mustafa, Mohd Rais; Othman, L.; Hodgson, W.C. (Elsevier, 2014)
Bungarus fasciatus is one of three species of krait found in Malaysia. Envenoming by B. fasciatus results in neurotoxicity due to the presence of presynaptic and postsynaptic neurotoxins. Antivenom, either monovalent or polyvalent, is the treatment of choice in systemically envenomed patients. In this study, we have isolated a postsynaptic neurotoxin which we named Î±-elapitoxin-Bf1b. This toxin has an approximate molecular weight of 6.9 kDa, with LCMS/MS data showing that it is highly homologous with Neurotoxin 3FTx-RI, a toxin identified in the Bungarus fasciatus venom gland transcriptome. Î±-Elapitoxin-Bf1b also shared similarity with short-chain neurotoxins from Laticauda colubrina and Pseudechis australis. Î±-Elapitoxin-Bf1b produced concentration- and time-dependent neurotoxicity in the indirectly-stimulated chick biventer cervicis muscle preparation, an effect partially reversible by repetitive washing of the preparation. The pA2 value for Î±-elapitoxin-Bf1b of 9.17 Â± 0.64, determined by examining the effects of the toxin on cumulative carbacol concentration-response curves, indicated that the toxin is more potent than tubocurarine and Î±-bungarotoxin. Pre-incubation of Bungarus fasciatus monovalent and neuro polyvalent antivenom failed to prevent the neurotoxic effects of Î±-elapitoxin-Bf1b in the chick biventer cervicis muscle preparation. In conclusion, the isolation of a postsynaptic neurotoxin that cannot be neutralized by either monovalent and polyvalent antivenoms may indicate the presence of isoforms of postsynaptic neurotoxins in Malaysian B. fasciatus venom.